2016
DOI: 10.1080/10942912.2016.1147459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified resistant starch of culinary banana on physicochemical, functional, morphological, diffraction, and thermal properties

Abstract: Resistant starch has received much attention for both its potential health benefits and functional properties. The present study revealed that the culinary banana can be a potential source for production of resistant starch type III. The results showed that resistant starch yield can be increased using debranching enzyme (Pullulanase EC 3.2.1.41) and hydrothermal process. The three repeated autoclaving and cooling (hydrothermal) cycles followed by storage at-20ºC, increased the resistant starch yield from 12.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 54 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…In addition, TDF content of AUEDF was higher than culinary banana bract (78.73 g/100 g), yellow passion fruit (71.79 g/100 g) and mango (74 g/100 g) (Begum & Deka, 2019;López-Vargas et al, 2014). Moisture content of PP, AEDF and AUEDF ranged from 8% to 10.23%, which is within the allowed range for storage without quality degradation (Khawas & Deka, 2017). Protein content in AUEDF was less as compared to PP and AEDF and might be due to high intensity ultrasound treatment in AUEDF which led to protein denaturation (Reis et al, 2015).…”
Section: Chemical Analysismentioning
confidence: 81%
“…In addition, TDF content of AUEDF was higher than culinary banana bract (78.73 g/100 g), yellow passion fruit (71.79 g/100 g) and mango (74 g/100 g) (Begum & Deka, 2019;López-Vargas et al, 2014). Moisture content of PP, AEDF and AUEDF ranged from 8% to 10.23%, which is within the allowed range for storage without quality degradation (Khawas & Deka, 2017). Protein content in AUEDF was less as compared to PP and AEDF and might be due to high intensity ultrasound treatment in AUEDF which led to protein denaturation (Reis et al, 2015).…”
Section: Chemical Analysismentioning
confidence: 81%
“…Fontes et al [37] described the shape of starch granules of banana from the green variety of Mysore as ellipsoidal in shape with irregular diameters that range between axes of 10 μm and 100 μm and smooth surface. Another study done by Khawas and Deka [38] indicated that isolated culinary banana starch experienced restricted swelling and solubility profile and was unstable during freezing and thawing cycles. However, the starch demonstrated a high pasting temperature which indicated that culinary banana starches have high gelatinisation temperature and resistance towards swelling.…”
Section: Functional Properties Of Resistant Starch Produced From Exotmentioning
confidence: 99%
“…Culinary banana starch exhibited a mixture of A-type and B-type polymorphs when observed under X-ray diffractometer. In addition, culinary banana starch has various functional groups which suggest C-type starch with a mixture of spherical and elliptical granules [38].…”
Section: Functional Properties Of Resistant Starch Produced From Exotmentioning
confidence: 99%
See 2 more Smart Citations